Analisis Bibliometrik Penghindaran Pajak - Nugraheni, Grace'tia Erich (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study presents a bibliometric analysis research on 'Tax Avoidance'. Tax avoidance is an effort to avoid taxes legally which does not violate tax regulations to minimize the tax burden by exploiting weaknesses in tax provisions. Tax evasion does not violate the provisions because it takes advantage of loopholes in the taxation requirements of a country. This study analyzes articles published from the Google Scholar database using publish or perish (PoP) software in the 2019-2023 period and are classified based on the topic, namely Tax Avoidance. This study uses secondary data. The sample used was 71 articles on tax avoidance. Data collection using the bibliometric analysis method has three specific applications of bibliometric analysis, including Mendeley, Publish or Perish (PoP) and Vosviewer. Generating network maps with VOSviewer using tax avoidance files in RIS format. To visualize the map using bibliographical data which is then displayed in network visualization map visualization, overlay visualization, density visualization. The existence of a bibliometric service using the VOSviewer application can provide various benefits, namely it can provide a reference for academics such as students, lecturers or accountants educators who will conduct research using bibliometric analysis.Keywords: Publish or perish, tax avoidance, vosviewer